Model Pendidikan Tradisionalisme Dalam Kegiatan Pengajian Kitab Kuning Ba'da Subuh di Masjid Al-Amin Sanggrahan Kepanjen Malang: Tinjauan Filsafat Pendidikan - Azis, Abdul (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2017)
In the context of the Islamic discourse in Indonesia, Islamic traditionalism is identified as a notion bound by exclusive traditional Islamic thought Traditionalism, is generally considered to be incompatible with modern times. Traditionalism is considered ancient and irrelevant to the times. More rational human beings, also the cause of this flow increasingly abandoned. But in reality, the implementation of education based on this flow is still common. One of them is the implementation of education in the form of recitation activity at Masjid al-Amin Sanggrahan Kepanjen Malang. Every day, hundreds of people arrived at dawn when it was cold and lazy to leave home - to attend the recitation. This is the opposite of the opinion that the flow is outdated, and is being abandoned. The pattern of education in the Al-Amin Sanggrahan Mosque is Traditionalism. It is based on the learning method used, the chosen learning content, the teaching position in the lesson, the position of the learners in the lesson, and the learning evaluation. However, according to the researchers, this traditional style should still be preserved. Because sometimes, when humans are fed up with all the modernity, they want to go back to the traditional things that are sometimes considered outdated and outdated. Keywords: Traditionalism, Educational Philosophy, Recitation activity